A rare presentation of acute-onset chronic inflammatory demyelinating polyneuropathy with the detection of anti-GM3 and anti-sulfatides antibodies: a case report - Sun, Ruohan; Meng, Yao; Li, Lingyu; Chen, Wei-hong; Xu, Jing; Lv, Peiyuan; Dong, Yanhong (Frontiers in Immunology, 2024)
Objectives Chronic inflammatory demyelinating polyneuropathy (CIDP) is an acquired immune-mediated neuropathy defined by clinical progression for more than 2 months. 16-20% of CIDP patients may present with rapidly progressive weakness that resembles GBS, known as acute-onset CIDP (A-CIDP). However, it is challenging to distinguish from GBS-TRF because of their similar clinical symptom and features. In this case review, we report a patient with A-CIDP with the detection of anti-GM3 and anti-sulfatides antibodies, which rarely have been in A-CIDP and may account for her progressive and recurrent symptoms. Methods We analyzed existing medical literature and described a clinical case of A-CIDP with antibodies positive. Results We reported a 56-year-old female presented with bilateral lower extremity weakness and distal numbness. She experienced similar symptoms four times and responded well to the IVIg therapy. Lumbar puncture demonstrated albumin-cytologic dissociation and EDX examination revealed multiple peripheral nerve damage. After ruling out other demyelination diseases, a diagnosis of A-CIDP was made. Discussion The antiganglioside and anti-sulfatide antibodies are involved in CIDP pathogenesis and can help to distinguish A-CIDP and other variants. To prevent secondary damage, it is important to monitor relapse and remission symptoms along the treatment line. A rare case of A-CIDP is discussed concerning the detection of anti-GM3 and anti-sulfatides antibodies, thus making a retrospective comparison of antibodies in some literature to understand A-CIDP better.